Active, Creative, Effective and Fun Learning with Character in 21st Century Skills - idawati idawati; Pandu Jati Laksono; Fatimatuzzahra Fatimatuzzahra (STAI Hubbulwathan Duri, 2022)
Character education is something that cannot be separated from 21st century learning. This study aims to explore the planning and implementation of Active, Creative, Effective and Joyful Learning (ACEJL) in creating a learning atmosphere that supports character content. The 21st century skills include critical thinking, creative, collaboration and communication (4C). A qualitative approach was used in this study with the research subject being 4 educators and 2 school principals teaching science and social studies subjects. This research was conducted on educators in two junior high schools in Palembang City. Data collection was taken by interviews, questionnaires and observations sourced from educators. An overview of the application of Active, Creative, Effective and Joyful Learning (ACEJL) in the success of a learning by adhering to the principles of 21st century skills that contain character which is a benchmark for educational success. The application of Active, Creative, Effective and Joyful Learning (ACEJL) was applied to both schools based on the Education Unit Level Curriculum and the 2013 Curriculum. Junior high school students in general are good and well-documented, but need adjustments to the latest curriculum (2013) to improve the quality of learning implementation plans that are in accordance with 21st century learning. The implementation of the Active, Creative, Effective and Joyful Learning (ACEJL) strategy with Character Loads for junior high school students is overall well implemented and needs to be improved on several things, namely the understanding of educators about the model and students so that it has an impact on the final learning outcomes.